(untitled) (Journal of Computational Mathematics, 2018)
In this paper, we present a block Lanczos method for solving the large-scale CDT subproblem. During the algorithm, the original CDT subproblem is projected to a small-scale one, and then some classical methods are employed to solve this small-scale CDT subproblem to get a solution, which can be used to derive an approximate solution of the original CDT subproblem. Theoretical analysis of the error bounds for both the optimal value and the optimal solution is also proposed. Numerical experiments are carried out, and it is demonstrated that the block Lanczos method is effective and can achieve high accuracy for large-scale CDT subproblems.